2019
DOI: 10.1177/2380084419870128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physician Oral Health Services on Dental Use and Expenditures under General Anesthesia

Abstract: Background: Despite early evidence touting the effectiveness of physician-provided oral health services (POHS), recent evidence suggests these services might have little impact on caries-related outcomes in children. General anesthesia (GA) is often used to treat early childhood caries and may be considered the most extreme utilization outcome. We sought to assess the impact of POHS utilization on dental GA utilization and expenditures. Methods: We used the Medicaid claims of a birth cohort of children born in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Compared to children who received preventive oral health services during medical well-child visits, children who received preventive care from a dentist had greater caries related treatment (4). Recent analysis questions the long-term benefits of physician provided preventive oral health services because over long follow-up periods, differences in caries related treatment and expenditures tend to attenuate (4,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to children who received preventive oral health services during medical well-child visits, children who received preventive care from a dentist had greater caries related treatment (4). Recent analysis questions the long-term benefits of physician provided preventive oral health services because over long follow-up periods, differences in caries related treatment and expenditures tend to attenuate (4,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In a country (KSA) where the prevalence of uncontrolled type II diabetes is among the highest in the world (77.7%) [ 33 ], oral health knowledge and dentalcare is, therefore, essential. In the same way early childhood caries (ECC) is a prevalent oral health problem with lifelong consequences that affect the child’s health and wellbeing [ 34 ], with financial burden on parents as it often/frequently necessitates the aid of general anesthesia [ 35 ]. Suboptimal knowledge about early signs of dental caries amongst health care providers may cause delayed referrals and place children at high risk of worsening health and chronic illness [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Turkey reported that 95% of them had sleep difficulties (12). DGA can reduce caries activity for short-to medium-term and improve children's oral health behaviour, nutritional and laboratory status, as well as their physical and mental health (13)(14)(15)(16). Given the low rates of postoperative complications, dental treatment under GA can be considered as an important and beneficial treatment option for children whose lack of cooperation makes conventional dental treatments impossible (17).…”
Section: Discussionmentioning
confidence: 99%